2020
DOI: 10.21203/rs.3.rs-23345/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Feasibility and acceptability of financial incentives and peer-led life skills training for improving adherence to antiretroviral therapy among adolescents living with HIV in Rwanda: A pilot study

Abstract: Background The Human Immunodeficiency Virus (HIV) is the leading cause of death among adolescents in sub-Saharan Africa. Despite the long-term benefits of antiretroviral therapy (ART), adherence remains low among adolescents due to challenges related to cost, acquisition, and treatment regimen. Sub-optimal adherence to ART is associated with the development of viral resistance, treatment failure, and increased morbidity and mortality. Financial incentives and life skills training interventions have shown earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Our retrospective cohort analysis of a youth-focused combined peer-support and economic incentive program did not identify any association between Adolescent Support Group membership and improved clinical outcomes. Two previous small pilot studies have assessed similar interventions, with one observing no clinical improvements and the other not reporting on clinical outcomes [21,22]. However, both studies identified potential non-clinical benefits to program participation, including psychosocial improvements and financial benefits, through qualitative interviews.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our retrospective cohort analysis of a youth-focused combined peer-support and economic incentive program did not identify any association between Adolescent Support Group membership and improved clinical outcomes. Two previous small pilot studies have assessed similar interventions, with one observing no clinical improvements and the other not reporting on clinical outcomes [21,22]. However, both studies identified potential non-clinical benefits to program participation, including psychosocial improvements and financial benefits, through qualitative interviews.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, although economic challenges are often cited as a barrier to treatment adherence, very few youth-focused intervention have assessed the impact of providing economic support on treatment outcomes [16][17][18][19]. Furthermore, although interventions designed to promote treatment adherence and clinical outcomes among youth are commonly include multiple complementary components [20], only two previous studies have combined peer support and economic incentives to support youth with HIV, and both were small pilot studies designed to assess feasibility and safety rather than effectiveness [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…17 The U.S. President's Emergency Plan for AIDS Relief (PEPFAR), the U.S. Agency for International Development (USAID), and their implementing partners have used HCD to promote HIV prevention and reproductive health globally. Examples include pre-exposure prophylaxis (PrEP) rollout in Zambia; 18,19 integrating sexual and reproductive health and HIV testing and prevention 20 with promoting ART adherence for adolescent girls and young women in Rwanda; 21 improving TB preventative treatment uptake among people living with HIV in Kenya; 22 and promoting HIV service uptake among men who have sex with men in the Philippines. 23 Although HCD is increasingly being employed to develop public health services and programs, it remains a novel approach to intervention development and dissemination in global health research.…”
Section: Introductionmentioning
confidence: 99%